Clinical and laboratory findings in patients with late diagnosis of AIDS - Yaumet Vidal Turruelles; Daniel González Rubio; Yaxsier de Armas Rodríguez (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction: Late diagnosis of HIV is a major problem with important consequences for the people infected with this virus and the society in general. Objectives: To characterize patients with late diagnosis of HIV infection and their evolution six months after diagnosis. Material and Methods: We conducted a prospective longitudinal study which included 248 cases with positive diagnosis of HIV infection during admission at the Pedro Kourí Tropical Medicine Institute between January 2015 and December 2016.  They were divided into two comparison groups which included patients with late diagnosis (n=79) and those with no late diagnosis (n=169) of the disease. Results: Advanced age and male sex were factors related to the late diagnosis of HIV infection. Fever (31.7%) and respiratory symptoms (20.3%) were the most frequent forms of presentation, whereas Pneumocystis jirovecii pneumonia was the disease with the highest incidence at the time of diagnosis. Half of the patients were found to have severe immunosuppression at the time of diagnosis. Patients with late diagnosis showed a significantly diminished survival six months after being diagnosed compared with those patients with early diagnosis. Viral load and CD4+ T count were laboratory parameters with a high predictive value of mortality. Conclusions: Late diagnosis of HIV leads to a high risk of mortality, which is higher in those with affectation of the viral load and low CD4+ T cell count.    Keywords: HIV, late diagnosis, viral load, CD4+ T cell count, longitudinal study, advanced age.